Taking morality seriously a defense of robust realism - Enoch, David (Oxford : Oxford University Press, 2011)
David Enoch develops, argues for, and defends robust realism - a strongly realist view of ethics and normativity, according to which there are perfectly universal and objective moral truths. He offers positive arguments for the view, and asserts that no other metaethical position can vindicate our taking morality seriously.
Title from home page (viewed on Sept. 5, 2011).
Also issued in print format.
Includes bibliographical references and index.
Keywords: Normativity (Ethics); Realism